Pengaruh Kualitas Audit terhadap Profitabilitas Perusahaan Perbankan Menggunakan Metode Regresi Linier pada Aplikasi SPSS - Najmuddin, Mohammad Ilham; Miranthi, Namira Putri; Putri, Negina Kencono; -, Agus Faturokhman (Jurnal Riset Akuntansi Soedirman, 2025)
Audit quality plays an important role in influencing a company's financial performance, especially in the banking sector where transparency and stability are prioritized. It is closely linked to the external auditor's ability to ensure accurate financial reporting, which directly impacts profitability and investor confidence. In Indonesia, the highly regulated banking industry imposes strict audit standards on companies listed on the Indonesia Stock Exchange (IDX) to maintain transparency and protect stakeholders. One prominent measure of audit quality is audit firm size, which is usually categorized into Big Four audit firms (KPMG, PwC, Deloitte, EY) and non-Big Four firms. Research shows that Big Four auditors, by utilizing their extensive resources and expertise, provide higher quality audits, which positively affect company profitability, which is often measured using Return on Assets (ROA). This study examines the effect of audit quality on the profitability of banking companies listed on the IDX during the period 2022-2023. A total of 47 samples of companies were analyzed using secondary data derived from the annual reports of these banks. The results of this study indicate that audit quality has a positive and significant effect on profitability, which means that when the company is audited by Big Four KAP, ROA will increase compared to companies audited by non-Big Four KAP. These results underscore the importance of high-quality audits in improving the financial performance of banking companies, and emphasize that companies should prioritize using reputable auditors to increase transparency and profitability.